Hospital doctors' and general practitioners' perspectives of outpatient discharge processes in Australia: an interpretive approach - Edwin Kruys; Chiung-Jung (Jo) (BMC, 2023)
Abstract Background Unnecessary delays in patient discharge from hospital outpatient clinics have direct consequences for timely access of new patients and the length of outpatient waiting times. The aim of this study was to gain better understanding of hospital doctors' and general practitioners' perspectives of the barriers and facilitators when discharging from hospital outpatients to general practice. Methods An interpretative approach incorporating semi-structured interviews with 15 participants enabled both hospital doctors and general practitioners to give their perspectives on hospital outpatient discharge processes. Results Participants mentioned various system problems hampering discharge from hospital outpatient clinics to general practice, such as limitations of electronic communication tools, workforce and workload challenges, the absence of agreed discharge principles, and lack of benchmark data. Hospital clinicians may keep patients under their care out of a concern about lack of follow-up and an inability to escalate timely hospital care following discharge. Some hospital clinicians may have a personal preference to provide ongoing care in the outpatient setting. Other factors mentioned were insufficient supervision of junior doctors, a patient preference to remain under hospital care, and the ease of scheduling follow-up appointments. An effective handover process requires protected time, a systematic approach, and a supportive clinical environment including user-friendly electronic communication and clinical handover tools. Several system improvements and models of care were suggested, such as agreed discharge processes, co-designed between hospitals and general practice. Recording and sharing outpatient discharge data may assist to inform and motivate hospital clinicians and support the training of junior doctors. General practitioners participating in the study were prepared to provide continuation of care but require timely clinical management plans that can be applied in the community setting. A hospital re-entry pathway providing rapid access to outpatient hospital resources after discharge could act as a safety net and may be an alternative to the standard 12-month review in hospital outpatient clinics. Conclusion Our study supports the barriers to discharge as mentioned in the literature and adds the perspectives of both hospital clinicians and general practitioners. Potential solutions were suggested including co-designed discharge policies, improved electronic communication tools and a rapid hospital review pathway following discharge.